Peran Ibu Rumah Tangga dalam Meningkatkan Ekonomi Keluarga di Jorong Padang Panjang Nagari Pariangan - Marleni Purnama Dewi; Jean Elikal Marna (Jurnal Salingka Nagari, 2023)
The role of housewives is important in the family, and has a very large contribution in the formation of a complete, solid, healthy, happy, prosperous family and provides benefits to the surrounding community. The purpose of this study was to determine the role of housewives in improving the family economy in Jorong Padang Panjang Nagari Pariangan. This study used descriptive qualitative method. With research informants 10 housewives who have additional work. The techniques used in data collection are observation, interviews and documentation. The analysis used in this research is data reduction, data presentation and conclusion drawing. In this study, the validity of the triangulation data was tested. The results showed that housewives have an important role in helping their husbands in improving the family economy. There are three types of business carried out by housewives, working as a tailor, working as a farm laborer and working as a trader. There is an increase in the economy after housewives work. The factors that cause housewives to work to improve the family economy are unmet family needs, many family dependents, children's school fees and future savings, lack of husband's income, and increasing husband's income.